Perbedaan Massa dan RPM Terhadap Adsorben Karbon Pelepah Sawit pada Pemurnian Minyak Jelantah - Fithry , Dwi Annisa; Haryanto, Bode; Febrisma, Anggun; Hutabarat, Astrina; Affandi, Rizki (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
The statistics center in 2021 stated that North Sumatra is the second largest palm oil-producing province in Indonesia with a plantation area of 1,373.30 Ha. The use of cooking oil in Indonesia in 2021 was 18.4 million tons and increased by 6% from the previous year. This research utilizes palm fronds for the manufacture of adsorbents in cooking oil refining. The method used is carbonization with the help of pyrolysis. The carbon is chopped into powder and divided by variations of 1.5, 3, and 4.5 grams. Each gram is stirred using a shaker with speed variations of 50, 70, and 100 rpm. Turbidity is tested using a turbidimeter once every 20 minutes for 180 minutes. The results of the analysis showed that the best adsorbent weight in reducing used cooking oil was 4.5 grams with a turbidity level of 15.5 NTU and stirring of 100 rpm.